Using collective impact in support of communitywide teen pregnancy prevention initiatives. Issue 2 (14th March 2016) - Klaus, Thomas W.; Saunders, Edward
Abstract: The Roots to Fruit of Sustainable Community Change (R2F) is a community development model for mobilizing efforts to effectively address teen pregnancy and other complex, controversial, social issues. The model is grounded in the authors' hypothesis that community engagement guided by a high-performing infrastructure leads to sustainable community change progressing through a measurable sequence. This article describes the model, the change sequence and their measures, and the integration of the collective impact framework. It also extends the collective impact framework by describing the R2F operationalization that facilitates long-term ownership of change through intentional, deep community participation. In addition, it demonstrates how collaborative approaches, including collective impact, can be used to address controversial complex social issues, such as teen pregnancy. Finally, it provides findings from the use of the new measures in an annual evaluation survey of communitywide teen pregnancy coalitions designed to support their continuous system learning and improvement.